Non-surgical treatment for tandem spinal stenosis: a systematic review protocol - Xin Liu; Lei Zhong; Xin Gou; Xu Hao Liu; Yuan Wei Dong; Xiao Long Yang; Jin Wen Zou; Hong Xia Fang (BMJ Open)
Background Tandem Spinal Stenosis (TSS) is a disease characterised by the narrowing of the spinal canal in two or more non-adjacent areas of the spine, often affecting both the cervical and lumbar vertebrae. Doctors and patients increasingly favour non-surgical treatments that have the function of relieving symptoms and improving outcomes. This systematic review aims to evaluate the effectiveness and safety of non-surgical therapies for TSS and comprehensively summarise existing evidence.Methods and analysis We will conduct comprehensive searches, both manual and electronic, of literature published up to 30 September 2024; database searches will commence after the publication of this agreement, with an estimated commencement date of 1 December 2024, and the end date is 31 May 2025, without language restrictions. Key databases such as MEDLINE, PubMed, EMBASE, Web of Science, Cochrane Library, WHO International Clinical Trial Registration Platform, China National Knowledge Infrastructure, China Biomedical Literature Database, China Scientific Journal Database and Wan-Fang Database will be explored. In addition, we will include resources such as library journals and conference abstracts. Following the identification and screening of all randomised controlled trials focusing on non-surgical treatments for TSS, two investigators will perform a meta-analysis of the included studies. The findings will be summarised as the risk ratio for binary data and the standardised or weighted mean difference for continuous data.Ethics and dissemination Ethical approval is not required, as the review does not involve individual patient data. The review’s findings will provide clinicians with evidence on using non-surgical treatments for TSS, disseminated through peer-reviewed publications or conferences.PROSPERO registration number CRD42024496634.